Histological Assessment of Selenium Protective Effect Against Diclofenac Sodium-Induced Nephrotoxicity in Rats - Albassit, Suhair; Al Laham, Shaza; Al-Manadili, Ahmad (Journal of Pharmacy and Nutrition Sciences, 2023)
Drug-induced nephrotoxicity is a matter of global significance, with widespread implications for human health. Non-steroidal anti-inflammatory drugs (NSAIDs), such as Diclofenac Sodium, are widely used but have been associated with numerous adverse effects, including those on the gastrointestinal tract, liver, and kidney. Selenium, an essential element in mammalian biology, has demonstrated antioxidant properties that enable it to antagonize the effects of free radicals. The present study aimed to investigate the potential protective effect of Selenium against Diclofenac Sodium-induced nephrotoxicity in rats. The study sample consisted of 32 male albino Wistar rats and was randomly divided into 4 groups: Control group, Diclofenac group (Dic group) (administered at a dose of 50 mg/kg I.M., for 3 days), Selenium group (Se group) (administered at a dose of 1 mg/kg I.P., for 8 days), and Diclofenac plus Selenium group (Dic + Se group). Rats were sacrificed on the 9th day. The results were analyzed with a significance level of p<0.05. The findings revealed significant tubular and glomerular injuries in the Diclofenac group compared to the control group. However, there was no statistically significant improvement observed in the Dic + Se group. In conclusion, the results of this study suggest that Selenium affords partial protection against Diclofenac Sodium-induced nephrotoxicity, but it is not sufficient to provide complete protection.